Generasi Ulu Al-Albab dan agenda penjanaan modal insan era kemajuan dan peradaban masa hadapan - Hussin, M.K.; Darusalam, G. (2011)

(untitled)
Ulu al-albab is an expression the Holy Quran directs to the faithful who are wise in saving the times and spurring the civilisation of the ummah. This paper explores the ideas of a structural leader which are valuable and futuristic in definition, characteristics and relevance in approach to generate insani (human) behaviour from the cognitive (intellectualism), affective (spiritual and emotive) and psychomotor (skills) aspects. The Ulu al-Albab generation has high potential to be a catalyst for the sustainability of future globalisation development. Besides accessing personal strength, excellent characteristics and wisdom, the Ulu al-Albab generation will utilize to master the fields of modern science and technology.